2016
DOI: 10.1097/dcr.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Anal Stenosis with Diamond Flap Anoplasty Performed in a Calibrated Fashion

Abstract: Diamond-flap anoplasty performed in a standardized and calibrated manner is a highly successful method for the treatment of anal stenosis caused by previous hemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
(14 reference statements)
1
19
1
4
Order By: Relevance
“…Assim como proposto por Gülen et al (2016), no paciente relatado foram realizadas incisões de pele em região perianal de modo a formar um retalho geométrico, onde este foi tracionado para transferir a mucosa retal ou pele perianal para o esfíncter anal, com o intuito de restaurar a elasticidade e o diâmetro anal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Assim como proposto por Gülen et al (2016), no paciente relatado foram realizadas incisões de pele em região perianal de modo a formar um retalho geométrico, onde este foi tracionado para transferir a mucosa retal ou pele perianal para o esfíncter anal, com o intuito de restaurar a elasticidade e o diâmetro anal.…”
Section: Discussionunclassified
“…No entanto, essas cirurgias apresentam inúmeras complicações como danos ao esfíncter anal externo e incontinência fecal (Carvalho et al, 2012;Rahal et al, 2007;Suess Junior et al, 1992). Em contrapartida, técnicas de correções de estenose anal em humanos utilizando avanços de retalhos geométricos apresentam bons resultados (Gülen et al, 2016).…”
unclassified
“…Although the final target for anal caliber has not been standardized, Gulen et al reported a clinical success rate of 88.9% with an eventual anal caliber of 25 to 26 mm in 18 consecutive patients. After 12-months of follow-up, the obstructed defecation syndrome scores were found to be significantly improved [ 25 ].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Se desarrolla cuando un tejido cicatricial restrictivo sustituye al anodermo, ocasionando una canal anal rígido y estrecho. Aunque hay descritas diferentes causas para la estenosis del canal anal, como los traumatismos, los tratamientos con radioterapia, las enfermedades venéreas o el uso crónico de laxantes, la causa principal de esta alteración es la realización previa de una hemorroidectomía, siendo en los adultos el factor desencadenante en el 90% de los casos (2) La estenosis del canal anal es una entidad clínica que se puede clasificar en congénita, primaria o secundaria (según el origen); aguda o crónica (por duración, reversibilidad); anatómica o funcional (según la etiología); leve, moderada o severa (según la severidad); y baja, media o alta (en función del nivel de afectación). Para las estenosis moderadas, se recomienda un manejo conservador empleando laxantes emolientes y/o suplementos de fibra.…”
Section: Discusionunclassified